2019
DOI: 10.1021/acsomega.9b03650
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Source Identification of Pu in River Basins in Southern China

Abstract: The 239+240Pu activities and 240Pu/239Pu atom ratios in surface sediments from the major river basins in southern China were analyzed to investigate the distribution and source of Pu. We clarified that the 239+240Pu activities in these river basins were very similar, however, only the 239+240Pu activities in the Jinjiang Basin were generally higher than other samples. Because of river transport function, the distribution of 239+240Pu activities in these river basins presented an increasing trend from the upstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…As we stated in Section , the current 237 Np/ 239 Pu atom ratio and 241 Am/ 239+240 Pu activity ratio are quite different from the reference values, so it is hard to identify the source directly. Previous studies , on Pu isotopes showed that the sources of Pu this study are PPG and global fallout (including Pearl River input) and the contribution of PPG was approximately 60–71% in NSCS, 49–69% in Pearl River Estuary, and 30 ± 10% in the major river basins of southern China. Due to the inseparable relationship between feature fingerprints of 237 Np and 241 Am and 239,240 Pu, we continue to use the reported data on the Pu isotope ratio in this study area and believed that the sources of Am and Np in this study area are also global sedimentation and PPG.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…As we stated in Section , the current 237 Np/ 239 Pu atom ratio and 241 Am/ 239+240 Pu activity ratio are quite different from the reference values, so it is hard to identify the source directly. Previous studies , on Pu isotopes showed that the sources of Pu this study are PPG and global fallout (including Pearl River input) and the contribution of PPG was approximately 60–71% in NSCS, 49–69% in Pearl River Estuary, and 30 ± 10% in the major river basins of southern China. Due to the inseparable relationship between feature fingerprints of 237 Np and 241 Am and 239,240 Pu, we continue to use the reported data on the Pu isotope ratio in this study area and believed that the sources of Am and Np in this study area are also global sedimentation and PPG.…”
Section: Resultsmentioning
confidence: 61%
“…North Equatorial Current (NEC) and Kuroku Current (KC) transport the Pu to the north South China Sea (NSCS) continuously supplied by Pacific Proving Ground (PPG). In addition to the ocean current input, the terrestrial nuclides brought by the Pearl River input also have a certain effect on the distribution of radionuclides in the downstream estuarine area . The sediments in NSCS are mainly terrigenous materials imported from Pearl River and coastal water systems, and their distribution is affected by coastal currents and tides. , Besides, Taishan and Yangjiang nuclear power plants are built on the coast of the NSCS.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the transport of coastal currents and sediment dynamics of fine particles might play an important role in controlling the spatial distribution of Pu isotopes in the surface sediment of the northern Yellow Sea (Xu et al 2018). In addition, the fine particles might absorb more total organic carbon content, and the total organic carbon content also has a certain influence on the distribution of 239+240 Pu activity (Wang et al 2019b).…”
Section: Methodsmentioning
confidence: 99%
“…Relationship between 239+240 Pu activity and 240 Pu/ 239 Pu atom ratio in the surface sediments of different seas and estuaries of China. Su and Huh 2002;Lee et al 2003;Wang and Yamada 2005;Hong et al 2006;Zheng and Yamada 2006;Liu et al 2011a;Pan et al 2011;Wu et al 2014;Wang et al 2017;Wang et al 2019b;Zhuang et al 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation